Professores do Ensino Fundamental e um Grupo de Trabalho: conflitos e histórias com atividades baseadas em categorias do cotidiano - Alonso Arinos de Moraes (2020)
The aim of this research is to produce a reading of the discussions, problematizations and productions of teachers and students, with activities based on categories of everyday life, in a working group with teachers from different disciplines. The Model of Semantic Fields is the main theoretical and methodological reference. In the period from 2018 to 2019, we produced our data through recordings in audio, video and observations of the Working Group meetings at the Municipal School Padre José Valentim, in the city of Campo Grande – MS. Activities based on everyday life were discussed, problematized and produced with elementary school teachers. From these movements, proposals for works with students were produced and implemented by teachers. The main considerations of the research are in the direction of two possibilities: conflicts and unfoldings. Conflicts of a Master's student in Mathematics Education, professor, pedagogical coordinator in a challenge of proposing and holding meetings with other teachers of his school, in conducting discussions and building other ideas in activities of the Program in Mathematics Education, in a writing that it expresses anguish and accomplishments of his everyday life that emerged, were invented, made explicit, taken from under the carpet. Unfolding of a possibility of in-service teacher education with (and not for) teachers from different disciplines of Elementary Education. The movements (discussions, problematizations, productions) with the teachers who are members of the working group, as well as the tasks and events carried out, offered possibilities to carry out actions with the school, considering the knowledge that teachers bring from their everyday lives, the ideas they have in relation to in-service teacher education with the school. The notion of the working group as a space for preparations, as an invitation, as a space for affections and inventions seems to us interesting, as it is made and constitutes a mutant in the context and demands to which it is operated. A last, not final, unfolding would be a need to invent other logics and narratives with this school that we have. Not in the direction of improving, making progress. Not also in the direction of disregarding what is produced there. In the direction of inventing, producing with what we have, that is, with the everyday lives of teachers, students, coordinators, and all the professionals who inhabit this space.